2012
DOI: 10.5539/ibr.v5n11p43
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Returns in Tehran Stock Exchange: The Influences of Size and Liquidity

Abstract: A study was carried out during 2001 to 2010 to illustrate the profit of momentum strategy in Tehran stock Exchange, and possibility of higher abnormal return based on past performance trends. In this study, the effects of two substantial variables including size and liquidity on profitability of momentum strategy in Tehran stock Exchange were investigated. The study was conducted in two sub-periods: 2005-2010, and 2007-2010. The first is due to a significant change in the number of stock companies after privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
0
2
1
Order By: Relevance
“…The results of this study are also consistent with the research of Jegadeesh & Titman (1993), Forner & Marhuenda (2003), Najmudin (2009), Fama & French (2012), and Bassiouny & Ragab (2014) which state that the 12month momentum strategy produced a positive and significant abnormal return. However, the results of this study do not support the results of previous studies conducted by Mansouri et al (2012) and Sasmikadewi and Dewi (2017) who s c r u t i n i z e t h a t negative abnormal returns were found on the momentum strategy in all periods.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are also consistent with the research of Jegadeesh & Titman (1993), Forner & Marhuenda (2003), Najmudin (2009), Fama & French (2012), and Bassiouny & Ragab (2014) which state that the 12month momentum strategy produced a positive and significant abnormal return. However, the results of this study do not support the results of previous studies conducted by Mansouri et al (2012) and Sasmikadewi and Dewi (2017) who s c r u t i n i z e t h a t negative abnormal returns were found on the momentum strategy in all periods.…”
Section: Resultscontrasting
confidence: 99%
“…Mansouri et al (2012) conducted a study on the effect of the size and liquidity of the company on the occurrence of profit momentum in the Tehran Stock Exchange. The results of this study by Mansouri et al (2012) were very contradictory because negative abnormal returns were found on the momentum strategy in the Tehran Stock Exchange in all periods. Forner & Marhuenda (2003) who conducted research on contrarian strategies, as well as momentum in the Spanish Stock Market, found that the 12-month momentum strategy produced positive and significant benefits.…”
Section: Introductioncontrasting
confidence: 57%
“…Henker (2012) melakukan penelitian dan menemukan bahwa strategi momentum tidak mendapatkan return yang signifikan selama periode penelitian. Mansouri, Tehrani, & Ansari (2012) melakukan penelitian di Tehran Stock Exchange yang menemukan bahwa strategi momentum itu tidak menguntungkan dalam semua periode hal ini juga didukung oleh penelitian Saputro & Badjra (2016).…”
Section: Pendahuluanunclassified